Vapor Recovery from Condensate Storage Tanks Using Gas Ejector Technology (Journal of Chemical Engineering, 2013)
This paper demonstrates a method of recovering the low pressure vapor from the condensate tanks in the Bibiyana gas field. This method uses a gas ejector as a device to compress the low pressure natural gas from the condensate tanks to an intermediate pressure, which would then be fed into the intermediated stage of the existing vapor recovery unit. Thus the natural gas will be saved which would have been otherwise flared. The amount of tank vapor is estimated by different methods, which shows a significant amount of gas is now being flared. Flaring of gas is a problem which entails both economic loss and environmental concerns. It is estimated that, on the average 190 MSCFD tank vapor can be recovered using the proposed method involving a gas ejector. Thus yearly saving would be about 68 MMSCF of natural gas. The equivalent heat energy saving is about 74.55X109 BTU. In terms of greenhouse gas emissions, this project will reduce about 1,112 tons of CO2 emissions per year in the gas plant locality. DOI: http://dx.doi.org/10.3329/jce.v27i1.15856 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 37-41